Risk assessment of recidivism in Latin America: assessing the reliability and validity of the Self-Appraisal Questionnaire - Trajtenberg, Nico (International journal of comparative and applied criminal justice, 2022)
Structured risk assessment tools are widely used across the criminal justice systems in western countries. However, little research has been conducted to validate these tools in low and middle-income societies. The aim of this study was to validate a cost-efficient risk assessment tool, the Self-Appraisal Questionnaire (SAQ) in Uruguay, Latin America. The SAQ was administered to a sample of 333 adult male inmates in combination with data from the case file information at the Prison System and self-report. Results showed significant evidence of SAQ’s score reliability (Cronbach α = .91) and concurrent validity with the Self-Report Psychopathy Scale Short Form (r = .62, p < .001). Furthermore, the SAQ showed satisfactory concurrent validity with official data and self-report data for recidivism (AUC = .71 and .75) and for violent recidivism (AUC = .76 and .77). Implications for future research in low and middle-income countries are discussed.